2018
DOI: 10.1186/s13104-018-3198-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with timing of umbilical cord clamping in tertiary hospital of Nepal

Abstract: ObjectiveDelayed umbilical cord clamping (DCC) (≥ 60 s) is recognized to improve iron status and neurodevelopment compared to early umbilical cord clamping. The aim of this study is to identify current umbilical cord clamping practice and factors determining the timing of clamping in a low-resource setting where prevalence of anemia in infants is high.ResultsA cross-sectional study design including 128 observations of clinical practice in a tertiary-level maternity hospital in Kathmandu, Nepal. Overall 48% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…The cutoff point for ECC was based on the observational study done in the same hospital that showed an average cord clamping time at 61 s [19]. The study site, Paropakar Maternity and Women’s Hospital, is a publicly funded hospital in Kathmandu, Nepal.…”
Section: Methodsmentioning
confidence: 99%
“…The cutoff point for ECC was based on the observational study done in the same hospital that showed an average cord clamping time at 61 s [19]. The study site, Paropakar Maternity and Women’s Hospital, is a publicly funded hospital in Kathmandu, Nepal.…”
Section: Methodsmentioning
confidence: 99%
“…These findings contradict advice of the Committee Opinion of The American College of Obstetricians and Gynaecologists, which has stated that delayed cord clamping in term infants increases the incidence of jaundice and the risk of associated complications. The Committee recommends that mechanisms to monitor and treat neonatal jaundice are in place before adopting the practice of delayed cord clamping .…”
Section: Discussionmentioning
confidence: 99%
“…The mothers were randomised during the second stage of delivery to either early cord clamping within 60 seconds (n = 270) or delayed cord clamping after 180 seconds (n = 270). The cut‐off for early cord clamping was based on an observational study held in the same hospital, which showed a mean and standard deviation cord clamping time of 61 ± 33 seconds . The study was approved by the institutional review board of the hospital and the ethical review board of Nepal Health Research Council (Ref 76/2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27] This review aimed to answer the questions: (a) What strategies are used to implement delayed cord clamping or cord milking in different settings around the world? [20][21][22][23][24][25][26][27] This review aimed to answer the questions: (a) What strategies are used to implement delayed cord clamping or cord milking in different settings around the world?…”
mentioning
confidence: 99%